The Disruption of Marketing Communication Concepts in the Marketing 3.0 Era: A Narrative Literature Review - Sandi, Yoki Famila (Open Access Indonesia Journal of Social Sciences, 2023)
The disruption in the concept of marketing communications in the marketing 3.0 era presented several significant changes in the method they interact and communicate with consumers. Marketing 3.0 places greater emphasis on the importance of social, environmental, and sustainability values in marketing communications. Brands must communicate their commitment to these issues and demonstrate concrete actions that support those values. This is important for building consumer trust and meeting their increasingly high expectations in terms of social and environmental responsibility. Marketing 3.0 involves consumers more actively in the process of communication and brand development. Consumers have a more significant role in designing products or services, providing input, and participating in brand initiatives. Brands must open and responsive communication channels to listen to consumers and involve them in the decision-making process. Story-based communication remains an effective approach in marketing 3.0. However, the stories a brand tells must be authentic, relevant and reflect the broader brand values. The story must be able to inspire and move consumers to take positive action and connect emotionally with the brand. Digital technology and social media have a central role in marketing communications in the marketing 3.0 era. Brands should leverage these platforms to reach consumers more effectively, spread their message, and interact with consumers directly. Technology also enables brands to collect and analyze consumer data to personalize communication messages and improve user experience.